Factors Associated with Recurrence of Varicose Veins after Thermal Ablation: Results of The Recurrent Veins after Thermal Ablation Study - R. G. Bush; P. Bush; J. Flanagan; R. Fritz; T. Gueldner; J. Koziarski; K. McMullen; G. Zumbro (The Scientific World Journal)
Background. The goal of this retrospective cohort study (REVATA) was to determine the site, source, and contributory factors of varicose vein recurrence after radiofrequency (RF) and laser ablation. Methods. Seven centers enrolled patients into the study over a 1-year period. All patients underwent previous thermal ablation of the great saphenous vein (GSV), small saphenous vein (SSV), or anterior accessory great saphenous vein (AAGSV). From a specific designed study tool, the etiology of recurrence was identified. Results. 2,380 patients were evaluated during this time frame. A total of 164 patients had varicose vein recurrence at a median of 3 years. GSV ablation was the initial treatment in 159 patients (RF: 33, laser: 126, 52 of these patients had either SSV or AAGSV ablation concurrently). Total or partial GSV recanalization occurred in 47 patients. New AAGSV reflux occurred in 40 patients, and new SSV reflux occurred in 24 patients. Perforator pathology was present in 64% of patients. Conclusion. Recurrence of varicose veins occurred at a median of 3 years after procedure. The four most important factors associated with recurrent veins included perforating veins, recanalized GSV, new AAGSV reflux, and new SSV reflux in decreasing frequency. Patients who underwent RF treatment had a statistically higher rate of recanalization than those treated with laser.